Efeito da acupuntura em indivíduos com desordem temporomandibular: avaliação eletromiográfica, nível de dor e aspectos psicológicos - Borin, Graciele da Silva (2011)
Temporomandibular disorders (TMD) can be described as a set of joint and muscle disorders in the region orofacial. Its etiology has multifactorial causes, and may be caused by associations among postural, psychological and structural factors. The acupuncture, because of the whole body approach, is presented as a treatment option indicated for the treatment of TMD patients, since this involves physical and psychosocial aspects. Thus, this study proposes to evaluate the use of acupuncture as a therapeutic intervention in the TMD, verifying its effect on the electrical activity of masticatory muscles, on the psychological aspects of pain level in individuals with this disorder. The study included 40 women aged between 20 and 40 years, with reports of pain in the temporomandibular joint and masticatory muscles. The first 20 volunteers were undergone to acupuncture twice a week for five weeks without interruption and after, they were reassessed. The results of these participants constituted the study group. The other volunteers received the treatment after the first group and their data, collected in the beginning and after 5 weeks without treatment, were utilized as control. The diagnosis of TMD was performed by applying the Diagnostic Criteria for Research of temporomandibular disorders (TMD-RD. Evaluations of the level of pain using a visual analog scale (VAS), severity index of Fonseca and the Craniomandibular Index and Electromyographic (EMG) assessment of masticatory muscles (masseter and anterior temporal bilaterally) were carried out. The evaluations were performed before (Av), soon after (R1) and after 10 session (R10) in the study group. The control group was evaluated at baseline (Av) and after 5 weeks (R10).The results of this study showed after acupuncture therapy 20% of the study group (SG) showed complete extinction of the diagnosis of TMD, while the control group (CG) retained 100% of individuals diagnosed with TMD. The results from the Axis I of RDC / TMD showed that SG has statistically significant increase in all mandibular movements, while in the CG there was a statistically significant reduction of these movements. Regarding the psychological aspects, evaluated by the Axis II of the RDC / TMD, it was verified a reduction in the intensity of chronic orofacial pain and improvements in physical symptoms including pain items in the SG, and the normal classification presented by 35% of participants at baseline rose to 60% at the reassessment. In the CG classification of mild symptoms increased from 10% to 30% and severe classification maintained their initial values. In the physical symptoms excluding pain items, the normal classification observed in 40% of participants increased to 75% after treatment. The severity of the disorder assessed by the Fonseca and craniomandibular indexes showed a significant reduction in SG (p = 0.00 and p = 0.004, respectively). The CG showed no significant differences in these indexes assessments. The EMG results observed in the rest mandibular position demonstrated statistically significant reduction in the electrical activity values in the left temporal muscle (p = 0.0062) immediately after an acupuncture session (R1) and higher electrical activity in the temporal muscles in relation to the masseter, with statistical significance for the left temporal muscle. After treatment (R10) there was a decrease in the EMG at rest, with statistical significance in the temporal muscles, however, these muscles maintained their electrical activity above the masseter. The CG had a higher electrical activity in the temporalis muscles both in the assessment and the reassessment; with statistically increase in the left temporal muscle and left masseter with the prevalence of left temporal muscle. No difference was observed in CG and SG (R1 and R10) during the maximum intercuspal position of the masticatory muscles. In SG, during chewing, there was a statistically significant decrease of activity in the right masseter after treatment. There was no statistical difference during chewing and during left unilateral chewing between CG and SG in the R1. In the SG (R10) there was a statistically significant decrease in electrical activity of the left temporal muscle in left unilateral chewing. From this study, it can be concluded that acupuncture is an effective technique in reducing pain level, the severity index and the electrical activity at mandibular rest in individualswithTMD.